Healthcare Utilization Among Infants Discharged From the Neonatal Intensive Care Unit: A Descriptive Cost Analysis - Nutan B Hebballi; Elenir BC Avritscher; Elisa Garcia; Andrew Bain; Marisa A Bartz-Kurycki; KuoJen Tsao; Mary T Austin (SAGE Publishing, 2023)
The cost of readmissions of neonatal intensive care unit (NICU) graduates within 6 months and a year of their life is well-studied. However, the cost of readmissions within 90 days of NICU discharge is unknown. This study's objective was to estimate the overall and mean cost of healthcare use for unplanned hospital visits of NICU graduates within 90 days of discharge A retrospective review of all infants discharged between 1/1/2017 and 03/31/2017 from a large hospital system NICUs was conducted. All unplanned hospital visits (readmissions or stand-alone emergency department (ED) visits) occurring within 90 days post NICU discharge were included. The total and mean cost of unplanned hospital visits were computed and adjusted to 2021 US dollars. The total cost was estimated to be $785 804 with a mean of $1898 per patient. Hospital readmissions accounted for 98% ($768 718) of the total costs and ED visits for 2% ($17 086). The mean cost per readmission and stand-alone ED visit were $25 624 and $475 respectively. The highest mean total cost of unplanned hospital readmission was noted in extremely low birth weight infants ($25 295). Interventions targeted to reduce hospital readmissions after NICU discharge have the potential to significantly reduce healthcare costs for this patient population.